The Islam of anthropology - Houston, Christopher (The Australian journal of anthropology, 2009)
Research on ‘Muslim societies’ is a controversial topic in the present, particularly given the US army’s current employment of anthropological experts in war zones under military occupation. In 2006 the UK Foreign Office, too, sought to include anthropologists in its worldwide research project entitled ‘Combating Terrorism by Countering Radicalization’, with grants given outside the normal process of research funding and differently assessed. In this article, I immodestly argue for how the discipline of anthropology should apprehend and analyse Islam in the present political context. The paper claims that anthropological research provides an antidote to the Islamophobia of much talk about Islam in the Australian public sphere, an Islamophobia originating not only from the right but from some leftists and feminists as well.